TEMPORAL AND SPECTRAL INDICATORS OF HEART RATE VARIABILITY OF TAEKWONDO ATHLETES - Shchedrina Yu.A. ,; Melnikov D.S. ,; Pavlenko A.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the features in the regulation of the heart rhythm of taekwondo athletes in transitional training at the stage of sports improvement. Methods and structure of the study. Taekwondo athletes of the Master of Sports (n=18) and candidates for the Master of Sports (n=2) of youth took part in the study at the end of the competition (fights were completed 2-3 weeks before the study). The temporal (variation range; stress index) and spectral parameters of heart rate variability were recorded using the Varicard hardware-software complex. Processing and analysis were carried out using the methods of mathematical statistics. Results and conclusions. The values of the variational range in male taekwondo masters of sports on average in the group are 300.30±98.02 ms, in the group of girls 244.41±64.83 ms; the value of the tension index in taekwondo athletes is 96.29±41.91 c.u., in taekwondo athletes - 91.09±21.77 c.u., which does not indicate a significant decrease in the functional potential of athletes, at the same time only in 2 athletes from 20 found the optimal structure of the spectrum: HF> LF> VLF, the rest of the study participants have a different spectrum structure scheme and indicate a state of fatigue, overtraining, psycho-emotional stress. Analysis of mean group values of temporal and spectral frequency parameters of heart rate variability does not allow one to objectively judge the state of regulatory systems. When considering personal values of heart rate variability, it is possible to assess the degree of tension of regulatory systems, the tolerance of realized training loads, the reserves of adaptation to the conditions of training and competitive activities.